Latent Cytomegalovirus-Driven Recruitment of Activated CD4+ T Cells Promotes Virus Reactivation - Jackson, Sarah E.; Chen, Kevin C.; Groves, Ian J.; Sedikides, George X.; Gandhi, Amar; Houldcroft, Charlotte J.; Poole, Emma L.; Montanuy, Inmaculada; Mason, Gavin M.; Okecha, Georgina; Reeves, Matthew B.; Sinclair, John H.; et al. (Frontiers in Immunology, 2021)
Human cytomegalovirus (HCMV) infection is not cleared by the initial immune response but persists for the lifetime of the host, in part due to its ability to establish a latent infection in cells of the myeloid lineage. HCMV has been shown to manipulate the secretion of cellular proteins during both lytic and latent infection; with changes caused by latent infection mainly investigated in CD34+ progenitor cells. Whilst CD34+ cells are generally bone marrow resident, their derivative CD14+ monocytes migrate to the periphery where they briefly circulate until extravasation into tissue sites. We have analyzed the effect of HCMV latent infection on the secretome of CD14+ monocytes, identifying an upregulation of both CCL8 and CXCL10 chemokines in the CD14+ latency-associated secretome. Unlike CD34+ cells, the CD14+ latency-associated secretome did not induce migration of resting immune cell subsets but did induce migration of activated NK and T cells expressing CXCR3 in a CXCL10 dependent manner. As reported in CD34+ latent infection, the CD14+ latency-associated secretome also suppressed the anti-viral activity of stimulated CD4+ T cells. Surprisingly, however, co-culture of activated autologous CD4+ T cells with latently infected monocytes resulted in reactivation of HCMV at levels comparable to those observed using M-CSF and IL-1β cytokines. We propose that these events represent a potential strategy to enable HCMV reactivation and local dissemination of the virus at peripheral tissue sites.